Harnessing microalgae for sustainable nutrition and ecosystem services in aquaponic systems: a blue–green approach to ecosystem health - Manoharan, Ramya; Somanathan Nair, Chythra; Nishanth, Drishya; Subramanian, Radhakrishnan; Ahmed, Zienab; Rastrelli, Luca; Xie, Xiu-Lan; Ren, Mao-Zhi; Jaleel, Abdul (Frontiers in Marine Science, 2025)
Aquaponics is a soilless farming approach that integrates aquaculture with hydroponics to produce food. In regions with limited arable land, aquaponics can help address food insecurity challenges. Both fish and plants are produced using aquaponic systems. The aquafeeds used to feed the fish in aquaponic systems are also the main source of nutrition for the plants. Currently, commercial aquafeeds such as fishmeal and fish oil are used in aquaponics, but they do not completely meet the nutritional requirements of plants. Additionally, commercial aquafeeds are expensive, and their production is unsustainable. This review focuses on the suitability of microalgae as a replacement for commercial aquafeeds and its role in meeting the nutritional requirements of plants growing in aquaponic systems. Microalgae production is sustainable and cost effective compared to commercial aquafeed production. Many studies have been conducted on the impact of microalgae-based feed on fish growth and its role as a biofertilizer and biostimulants for plant growth. However, using microalgae as aquafeed for the development of both fish and plants in aquaponic systems remains underexplored. This review aims to provide insights into the dual role of microalgae in aquaponics—enhancing fish nutrition while supplementing plant nutrient requirements. Although some micronutrient gaps may persist, further optimisation could help make aquaponic systems more efficient and sustainable.